Let:
y=2x+18 (1)
4x+5y=20 (2)
replace (1) into (2)
4x+5(2x+18)=20
Using distributive property:
4x+10x+90=20
Add like terms:
(4x+10x)+90=20
14x+90=20
subtract 90 from both sides:
14x+90-90=20-90
14x=-70
Divide both sides by 14:
14x/14=-70/14
x=-5
Finally, replace the value of x into (1)
y=2(-5)+18
y=-10+18
y=8
Let:
2x+2y=6 (1)
3x-5y=25 (2)
From (1) let's solve for x:
subtract 2y from both sides:
2x+2y-2y=6-2y
2x=6-2y
Divide both sides by 2:
x=(6-2y)/2
x=3-y (3)
Replace (3) into (2)
3(3-y)-5y=25
Using distributive property:
9-3y-5y=25
Add like terms:
9+(-3y-5y)=25
9-8y=25
subtract 9 from both sides:
9-8y-9=25-9
-8y=16
Divide both sides by -8:
(-8y)/(-8)=(16)/(-8)
y=-2
Finally, replace the value of y into (3)
x=3-(-2)
x=3+2
x=5